A MEDIATING TRUST: HOW EASE OF USE AND SERVICE FEATURES INFLUENCE TRANSACTIONAL INTEREST ON THE MYBCA MOBILE APP - Malini, Helma; Aldora Sianturi, Yosia (Magister Manajemen Universitas Islam Malang, 2025)
The rapid evolution of financial technology has positioned the MyBCA mobile application as a central tool for daily transactions in Indonesia. However, despite its widespread adoption, challenges related to usability, service features, and overall reliability can still impact user trust and subsequently their interest in transacting. This study addresses a crucial gap by empirically investigating the complex relationships among ease of use, service features, trust, and users' transaction interest within the context of the MyBCA mobile application. Specifically, it aims to determine the extent to which ease of use and service features influence transaction interest, and whether trust acts as a mediating variable in these relationships. This research employed a quantitative causal-associative approach, collecting data from a sample of 150 MyBCA Mobile app users in Indonesia through an online questionnaire using a purposive sampling method. The collected data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The empirical findings reveal nuanced relationships between the constructs. Ease of use was found to have a significant direct positive effect on transaction interest. However, its effect on trust was not significant, suggesting that basic usability is a customer expectation rather than a trust builder. Conversely, service features significantly affect trust but have an insignificant direct effect on transaction interest, implying that features build confidence, but not necessarily immediate action. Importantly, trust has a significant positive effect on users' interest in transacting. Ultimately, the study found a full mediation effect for both relationships, confirming that trust significantly mediates the influence of both ease of use and service features on transaction interest. This novel perspective suggests that while usability and features are essential, their full potential in driving transactional behavior is realized only through the establishment of trust. The conclusion is that digital banks must integrate intuitive design with robust, reliable features and strong security to foster the trust critical for sustained user engagement.